Revisit Intention Shaped by Digital Appeal and Interpersonal Recommendation - Ni Made Karisma Surya Putri; Ida Ayu Oka Martini (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2026)
This study proposes a research model and empirically examines the factors influencing patients’ revisit intention toward private dental practices. Drawing upon the Theory of Planned Behavior (TPB) and Customer-Based Brand Equity (CBBE), the study develops a theoretically grounded framework to analyze how communication strategies shape behavioral intentions. Using a quantitative approach, data were collected through questionnaires administered to 131 patients who had visited private dental practices in Bali Province within the past six months. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The results reveal that word of mouth significantly influences patients’ revisit intention both directly and indirectly, while social media content affects revisit intention through the mediating role of brand image. These findings underscore the critical role of brand image in translating communication efforts into patients’ behavioral intentions. The study provides managerial insights for private dental practice managers in designing effective, adaptive, and sustainable communication strategies to strengthen brand image and enhance patients’ likelihood of returning.